Pengaruh Metode Quenching dan Tempering Terhadap Kekerasan Material Hot rolled Plate (HRP) Steel - Nurhidayat, Akhlis Rahman Sari; Laksana, Nur Akhlis Sarihidaya; Yurianto, Yurianto (Infotekmesin, 2023)
Hot rolled plate steel as a material to be used for steel armor needs to have the characteristics of a high hardness value. Medium carbon steel as the basic material is quenched at a temperature of 900 oC and tempering is carried out at a temperature of 125 oC and 175 oC with a holding time of 30 minutes. The Ms value is a benchmark for changes in martensite which is influenced by the constituent elements of the material. The use of water as a quench medium changes the structure of austenite to martensite. The martensite structure that occurs increases the optimum hardness value in HRP Steel material. The tempering process carried out above the Ms value causes a decrease in the hardness value. The highest hardness value was obtained in the quenching process with 542 HV which was influenced by the distribution of martensite. The decrease in hardness value occurs due to the tempering process, the average hardness value at temper 125 oC is 524.4 HV and 175 oC is 524 HV.